The kitchen fire prevention system using a global system for mobile - Rosnee Ahad; Nur Amani Lowe Mohd Shafiq Lowe; Mohamad Zaid Mustafa; Sri Sumarwati (Journal of Engineering and Applied Technology, 2021)
Fire is one of the disasters that cause property loss and casualties. Based on statistical analysis, the cases related to Liquefied Petroleum Gas (LPG) fires caused by the stove, are repeated every year. There is no fire prevention system in the house, usually in the kitchen, applied as a safety and prevention measure to prevent fire. Therefore, this quantitative study aims to develop a prototype of the kitchen fire prevention system using the Global System for Mobile (GSM) modem to reduce the risk of fire in the living room caused by the kitchen appliances. The development of this project refers to the five steps in the Software Development Life Cycle (SDLC) method which is needs analysis, design, implementation, testing, and evaluation. The results show that the prototype combines two types of sensors namely MQ135, and LM35, where it works simultaneously in two conditions. Under "Reminder 1", when the MQ135 detects smoke above 100 while LM35 exceeds 40ºC, the Arduino Uno microcontroller directs the DC motor to turn off the kitchen valve automatically. Besides, GSM simultaneously sends the first warning message to the user. In the "Warning 2" state, when MQ135 detects smoke above 200 while LM35 is above 50ºC, GSM sends a second warning message. The findings of this study indicate that experts recommend improvements to use the 5V power supply from the AC / DC adapter. Overall, experts argue that the prototype design is clear and easy to understand and the prototype of the stove fire prevention system is suitable for development for safety and notification purposes.